2022
DOI: 10.3390/jpm12010065
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Genomic Tissue-Based Biomarkers in the Treatment of Localized Prostate Cancer

Abstract: In localized prostate cancer clinicopathologic variables have been used to develop prognostic nomograms quantifying the probability of locally advanced disease, of pelvic lymph node and distant metastasis at diagnosis or the probability of recurrence after radical treatment of the primary tumor. These tools although essential in daily clinical practice for the management of such a heterogeneous disease, which can be cured with a wide spectrum of treatment strategies (i.e., active surveillance, RP and radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The Newcastle Ottawa Scale (NOS) recommended by the Agency for Healthcare Research and Quality will be employed to assess the quality of articles, as previously reported by Ingrosso et al [ 18 ]. A total of 9 key criteria will be judged.…”
Section: Methodsmentioning
confidence: 99%
“…The Newcastle Ottawa Scale (NOS) recommended by the Agency for Healthcare Research and Quality will be employed to assess the quality of articles, as previously reported by Ingrosso et al [ 18 ]. A total of 9 key criteria will be judged.…”
Section: Methodsmentioning
confidence: 99%
“…Advanced methods using genetic profiling, for example, provide a wealth of information but have shown limited success in predicting the prognosis of cancer patients 14 20 . The poor predictive power may be attributed to the vast genetic heterogeneity of tumors, which makes it extremely difficult to identify a unique set of mutations that provide reliable prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…In patients that have already been diagnosed with cancer, it can be challenging to stratify those with tumors that are less likely to progress from patients with tumors that are more aggressive and therefore require treatment intensification; tumor heterogeneity contributes greatly to this problem. While the early diagnosis of cancer is crucial for enhancing the survival of patients, the identification of biomarkers at the time of diagnosis that can give an indication of cancer aggressiveness is possibly the greatest unmet clinical need for many cancer types [2,7]. Prognostic biomarkers identify the likelihood of disease recurrence or progression; these factors are crucial to decision-making processes in the clinic, helping clinicians determine the most appropriate treatment for each patient.…”
mentioning
confidence: 99%
“…Prognostic biomarkers identify the likelihood of disease recurrence or progression; these factors are crucial to decision-making processes in the clinic, helping clinicians determine the most appropriate treatment for each patient. Several publications within this Special Issue explored prognostic biomarkers, focusing on the development of prognostic tissue-based biomarkers in ovarian cancer [8], prostate cancer [2,7] and renal cell carcinoma [9], in addition to prognostic liquid-based biomarkers in prostate cancer [2], bladder cancer [10] and head and neck cancer [11]. Studies published within the Special Issue also show how cancer prognosis is moving towards the use of imaging, rather than relying on tissue/liquid biomarkers alone [12].…”
mentioning
confidence: 99%